Proposed Strategy for Reducing Expired Consumables Using Kepner-Tregoe Approach and Analytical Hierarchy Process - Enggar Abimantrana Prabaswara; Gatot Yudoko (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
As an aerospace company in Indonesia, AE Company has a goal expand its capabilities and collaboration for various aerospace manufacturing projects. However, AE Company could not fully utilize its production capacity due to occasional production delays and large quantity of consumables procured. This condition affects AE Company’s capability to fully utilize limited shelf-life consumables, leading to financial loss of more than US$200,000 worth of consumables due to the expiration. The objectives of this study are to propose an improvement strategy to reduce expired consumables at AE Company, focusing on the limited shelf-life consumables which has maximum shelf-life of twelve months by using Kepner-Tregoe approach and Analytical Hierarchy Process (AHP). Root Cause and alternative solution is obtained using Kepner-Tregoe approach, while the preferred alternative solution is chosen using Analytical Hierarchy Process (AHP). From the Analytical Hierarchy Process (AHP), it is decided that “Optimization of Procurement Cycle and Quantity” is chosen as the alternative solution to reduce expired consumables at AE Company.